A Novel TVA-REPSO technique in solving generators sizing problems for south Sulawesi network - Jamian, J.J.; Mohd Zin, A.A.; Saini, M.; Mustafa, M.W.; Mokhlis, Hazlie (Nowoczesna technika TVA-REPSO w rozwiaogonekzaniu zagadnienia doboru rozmiarÃ³w generatora w sieci elektroenergetycznej PoÅudniowej Sulawesi, 2013)
This paper present a novel optimization method, Time Varying Acceleration - Rank Evolutionary Particle Swarm Optimization (TVAREPSO) in solving optimum generator sizing for minimising power losses in the transmission system of South Sulawesi, Indonesia. A comparison between the proposed method and three other methods was done in order to find the best method to optimize the generators' output size. The results show that the TVA-REPSO algorithm can obtain the same performance as PSO but it only required shorter computing time and can converges faster than the original PSO.